Keterlibatan Mediator Non Hakim Dalam Menangkal Perceraian Di Pengadilan Agama Banyuwangi - Ali, M. Irwan Zamroni (Kertha Patrika, 2023)
The aim of this study examines the extent of mediation role carried out by non-judge mediators in suppressing the divorce rate that occurs at the Banyuwangi Religious Court. This research is empirical legal research that uses qualitative research methods with a case approach. The research location was conducted at the Banyuwangi Religious Court on Jl. Jaksa Agung Suprapto No. 52, Penganjuran, Banyuwangi District, Banyuwangi Regency. The data were obtained by using observation, interview, and documentation techniques. The validity of the data was carried out using a source triangulation technique, where the researcher guided several lecturers and related parties such as non-judge mediators and the chairman of the Banyuwangi Religious Court. The results of this study found that the divorce rate in Banyuwangi Regency was very high which was influenced by economic factors, the occurrence of continuous disputes or quarrels, and the death of one of the parties. In addition, the role of non-judge mediators in mediating to reduce the number of divorce cases is less influential. This is evidenced by the results of the percentage of successful mediation in 2019 which is still very low. On the other hand, the parties who wish to file for divorce have previously coordinated so that one of the parties is not present in the trial process so that the divorce process will be faster.